Pelvic Floor Dysfunction in Athletes: Risk Factors, Prevention, and Rehabilitation – A Narrative Review - Jankowski , Mikołaj; Bogdan, Klaudia; Janicka, Urszula; Ciepluch, Natalia; Słomiński, Szymon; Toczek, Wiktoria; Olszówka, Magdalena; Dziugieł, Sonia (Quality in Sport, 2026)
Pelvic floor dysfunction (PFD) is increasingly recognized among athletic populations of both sexes, particularly in sports characterized by repetitive high-impact loading, sustained elevations in intra-abdominal pressure, and high training volumes. Clinical manifestations include urinary incontinence, pelvic pain, voiding disturbances, and, less frequently, prolapse-related symptoms, which may negatively affect performance and quality of life. Although physical activity confers substantial health benefits, sport-specific mechanical and neuromuscular demands may exceed pelvic floor adaptive capacity in susceptible individuals. This narrative review synthesizes contemporary evidence (2020–2025) regarding the epidemiology of PFD in athletes, underlying biomechanical and neuromuscular mechanisms, sport-specific risk factors, and evidence-based strategies for prevention and rehabilitation. Practical implications for screening, training-load management, and multidisciplinary care in athletic populations are discussed.